Importance of the integrated test in the Down's syndrome screening algorithm - Springer, Drahomira; Loucky, Jaroslav; Tesner, Pavel; Cutka, David; Stejskal, David; Gregor, Vladimir; Zima, Tomas (Journal of medical screening, 2018)
OBJECTIVE: In the Czech Republic, over 97% of all pregnant women undergo some type of antenatal screening for Down's syndrome. In about 95% of cases with a confirmed fetal chromosomal abnormality, the pregnancy is terminated. The most commonly used test is the first trimester combined test. We investigated the impact of implementing an integrated sequential test to improve the detection of Down's syndrome pregnancies. METHODS: Data on the incidence of congenital defects, number of births, and affected pregnancies terminated are recorded in the National Registry of Congenital Anomalies. Anonymous data on cases of Down's syndrome diagnosed antenatally or postnatally between 2010 and 2015 in one of the large antenatal care centers were analyzed. RESULTS: There were 600 diagnoses of Down's syndrome (5.7 per 1000 births), 90% of which were made antenatally. Of antenatally detected cases, 80% were indicated for diagnostic procedure by multimarker screening results. In the multimarker screen positive group, 75% cases were first trimester positive and 25% second trimester positive (most of these had positive integrated test results). Among Down's syndrome cases indicated for antenatal diagnosis by multimarker screening results 6.25% (n = 26) were first trimester negative, and became positive after integration with the second trimester screening results. CONCLUSIONS: Results from five major Czech antenatal centers confirm that an integrated sequential test would detect 80-85% of Down's syndrome fetuses in the first trimester and at least an extra 5-10% of Down's syndrome pregnancies in the second trimester of pregnancy. These are important data that should be considered in implementing the national antenatal screening program.
Keywords: lidský choriogonadotropin, beta podjednotka; Peptide Fragments; False Positive Reactions; Pregnancy Trimester, First; Down Syndrome; Cell-Free System; věk matky; Humans; těhotenství; těhotenský plazmatický protein A; první trimestr těhotenství; algoritmy; Algorithms; Prenatal Diagnosis; měření nuchální translucence; Ultrasonography, Prenatal; ultrasonografie prenatální; ženské pohlaví; rozhodování; peptidové fragmenty; Pregnancy-Associated Plasma Protein-A; falešně pozitivní reakce; Chorionic Gonadotropin, beta Subunit, Human; Mass Screening; druhý trimestr těhotenství; Czech Republic; Registries; Adult; prenatální diagnóza; dospělí; Česká republika; Maternal Age; Nuchal Translucency Measurement; lidé; Decision Making; bezbuněčný systém; Pregnancy; Pregnancy Trimester, Second; plošný screening; Downův syndrom; Female; registrace